ANALISIS SOFT SKILLS MAHASISWA PROGRAM STUDI PENDIDIKAN GURU MADRASAH IBTIDAIYAH PADA ASISTENSI MENGAJAR - Istianah, Istianah (Sasangga: Jurnal Pendidikan dan Pembelajaran, 2024)
Soft skills play an important role in an individual's success, including for a teacher. Therefore, as prospective teachers, Pendidikan Guru Madrasah Ibtidaiyah (PGMI) students should possess good soft skills starting from their time in university. The implementation of the Teaching Practice can serve as a platform for students to enhance their experience, awareness, and skills in the teaching field, and during this Teaching Practice, PGMI students' skills are maximally tested. This study aims to provide an overview and analyze the level of soft skills among PGMI students from the 2019 cohort at UIN Antasari who participated in the Teaching Practice during the 2021/2022 academic year, from July 18 to September 2, 2022. The research method used is a survey sampling method with a descriptive quantitative approach. The number of respondents in this study was 36. The results of the study show that the soft skills of PGMI students from the 2019 cohort consist of personality competencies (intrapersonal skills) and social competencies (interpersonal skills), which are generally categorized as moderate. The detailed categorization results of soft skills from the intrapersonal skills aspect are as follows: 14% of students fall into the high category, 67% fall into the moderate category, and 19% fall into the low category. Meanwhile, for the categorization of soft skills in the interpersonal skills aspect, 19% of students fall into the high category, 69% fall into the moderate category, and 11% fall into the low category. Several factors can influence the quality of an individual's soft skills, including organizational experience, leadership, lecturer competence, learning behavior, and learning motivation